The New Canada Not-for-profit Corporations Act; An Overview - Lynne Golding (Law & Governance, 1999)
The current legislative regime governing the federal not-for-profit sector has not undergone any significant modification since 1917. On November 15, 2004, following much public consultation, the federal government introduced An Act Respecting Not-for-profit Corporations and Other Corporations Without Share Capital (Bill C-21) (the "Canada Not-for-profit Corporations Act") (hereinafter "the Act") which provides a modern system of corporate governance for federal not-for-profit corporations and special act corporations without share capital currently regulated by the Canada Corporations Act. The federal government has predicted that it will take more than a year for the new legislation to be passed, and amendments and changes to its current provisions remain likely as it proceeds through the legislative process. The following summary highlights some of the most important aspects of this highly detailed and comprehensive piece of legislation.